Sony Computer Science Laboratories : sustaining a culture and organization for fundamental research - Toriyama, Masahiro, active 2020; Sawhney, Mohanbir S.; Kruse, Katharine (London : Kellogg School of Management, 2020)
In late 2019, Dr. Hiroaki Kitano, the president and director of research at Sony Computer Science Laboratories (Sony CSL), had decided he would be stepping down from his position soon. Sony CSL, a small blue-sky fundamental research facility funded by Sony, had always operated on the strength of the trust between Sony's CEO and the lab's director. Sony had been hands-off in its management, leaving Kitano to hire, fire, fund, and evaluate the lab's researchers and project portfolio at his own discretion. Now that he was stepping down, however, he worried that Sony CSL could not withstand his departure. Kitano wanted to make a transparent plan for the organization's future before he handed off Sony CSL to his successor. That plan involved three key decisions. First, what should be the optimal structure and governance of Sony CSL? Should it maintain its independence and autonomy, or should it align more closely with Sony's business priorities? Second, how could Sony CSL scale its impact on Sony and society at large, given its small size? Finally, should Sony CSL establish some standard methods of measuring project success and strength of the portfolio? In making these decisions, Kitano wanted to ensure that he preserved the unique culture that had allowed Sony CSL to pursue path-breaking research and innovation.
Originally Published InToriyama, M., Sawhney, M., & Kruse, K. (2020). Sony Computer Science Laboratories:Sustaining a Culture and Organization for Fundamental Research. 5-120-007. Evanston, IL: Kellogg School of Management, Northwestern University.
Includes bibliographical references.
Description based on XML content.
Keywords: elektronické knihy; electronic books; Sony Computer Science Laboratories -- Case studies; Corporate culture -- Case studies; Industrial management -- Case studies